2021
DOI: 10.1021/acs.jpcc.1c03274
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Defect Chemistry of (Pu,Am)Ox

Abstract: The β decay of 241 Pu to 241 Am results in a significant ingrowth of Am during the interim storage of PuO 2 . Consequently, the safe storage of the large stockpiles of separated Pu requires an understanding of how this ingrowth affects the chemistry of PuO 2 . This work combines density functional theory (DFT) defect energies and empirical potential calculations of vibrational entropies to create a point defect model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In a previous study, Am( iii ) was found to be accommodated in PuO 2 as substitutions on Pu sites, with a net charge of −1 (Am Pu 1− ). 37 The ratio of Am( iv ): Am( iii ) in (Pu,Am)O 2± x was found to vary with external conditions and total Am concentrations. However, in conditions where Am( iv ) is the dominant oxidation state, Am( iii ) concentrations remain high, and Am( iii ) is dominant in hypo-stoichiometric PuO 2− x , due to reduction of Am( iv ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous study, Am( iii ) was found to be accommodated in PuO 2 as substitutions on Pu sites, with a net charge of −1 (Am Pu 1− ). 37 The ratio of Am( iv ): Am( iii ) in (Pu,Am)O 2± x was found to vary with external conditions and total Am concentrations. However, in conditions where Am( iv ) is the dominant oxidation state, Am( iii ) concentrations remain high, and Am( iii ) is dominant in hypo-stoichiometric PuO 2− x , due to reduction of Am( iv ).…”
Section: Resultsmentioning
confidence: 91%
“…). 37 The ratio of Am(IV): Am(III) in (Pu,Am)O 2AEx was found to vary with external conditions and total Am concentrations. However, in conditions where Am(IV) is the dominant oxidation state, Am(III) concentrations remain high, and Am(III) is dominant in hypo-stoichiometric PuO 2Àx , due to reduction of Am(IV).…”
Section: Resultsmentioning
confidence: 91%
“…Investigations dealing with the local environment and valences of the cations in (Pu,Am)O 2Àx indicated that Am occupies the Pu sites in the oxide and will reduce to Am(III) prior to any reduction of Pu(IV). 154,186 In comparison to the theoretical a 0 values of 5.396 Å and 5.373 Å for PuO 2 and AmO 2 , respectively, it was demonstrated that the presence of Am in (Pu 1Ày , Am y )O 2Àx may induce an increase in the lattice parameter for the oxide studied (a 0 ¼ 5.400 and 5.411 Å for Am/(Pu+Am) ¼ 0.008 and 0.2, respectively). 187 At high temperature, low Am concentration and low oxygen-to-metal ratio, Am is mainly found in the +III state.…”
Section: Comments On Structural Variations Induced By Radiolysis For ...mentioning
confidence: 83%
“…The Brouwer diagrams presented in this investigation that used Fermi-Dirac statistics gave subtle differences, with enhanced accuracy but do not fundamentally alter the picture previously reported in literature when considering no lithium [23]. The ability to stipulate a defect species concentration is novel to the Brouwer diagram script created by Murphy et al [30]. This is particularly advantageous as it provides a basis for comparison in real world applications where lithium concentrations are added to coolant water within a nuclear reactor.…”
Section: Discussionmentioning
confidence: 75%
“…DFT can also provide electronic information concerning the perfect supercell structures including band gap, valence and conduction bands, which are used in the creation of the Brouwer diagram, using Fermi-Dirac statistics to provide electron and hole concentrations upon which charge defect equilibria could be attributed. A novel aspect of the Defect Analysis Package V2.7 script created by Murphy and Neilson [30] is that a particular defect concentration may be stipulated where all other defect equilibria, including those of electrons and holes, are calculated. In the case of this investigation, lithium concentrations are stipulated from 10 -3 to 10 -11 per ZrO2 formula unit and a temperature of 635K was used for all calculations as a normal (water) operating temperature of a PWR [31].…”
Section: Brouwer Diagramsmentioning
confidence: 99%